Salahfaham tentang kedudukan wanita Muslim (misunderstanding on the position of Muslim women) - Nor, M.R.M. (Persatuan Ulama Malaysia, 2011)
The image of Muslim women is always an interesting subject of research. Some scholars consider that Islam is the religion which has no clear stand on women. What make it worst is that some Muslim countries and societies have been portrayed as not ‘women friendly’. The image of Muslim women such as obligation to wear headscarf / veil, forced to sit at home alone, can not drive vehicles, are parts of common things that always been raised. Is the religion has no clear stand on women’s right? This paper seeks to investigate this matter and would provide arguments which women were given safety in religion and their rights were established since the revelation came to Muhammad.